Ensuring safe prescribing of controlled substances for pain following surgery by developing a transitional pain service. (March 2015) - Huang, Alexander; Katz, Joel; Clarke, Hance
SUMMARY : Chronic postsurgical pain is a significant complication following major surgery, which impairs patient's quality of life. Opioid medications are the mainstay of most postoperative analgesic regimens. Growing evidence suggests inherent risks associated with opioids used for postoperative pain. Beyond common opioid-related side effects, increased mortality in the community and developing persistent opioid problems have been reported. There is a paucity of literature regarding the safe and effective management of postoperative pain as patients transition from the hospital to home/community. The introduction of a transitional pain service, whose aim is to optimize pain control, monitor and appropriately wean patients off opioid medications, prevent unnecessary readmissions post-discharge, and reduce disability associated with the development of chronic post surgical pain, will be of benefit to patients and the healthcare system.